Schottky behavior of novel synthesized aligned zinc oxide nanorod arrays and aligned carbon nanotube arrays for mesfet device / Salina Muhamad - Muhamad, Salina (Institute of Graduate Studies, UiTM, 2012)
This study is carried out to introduce new active layers in a Schottky diode for a metal-semiconductor field effect transistor (MESFET) device structure, which are novel aligned zinc oxide (ZnO) nanorod arrays and aligned carbon nanotubes (CNT) arrays. Both nanomaterials are successfully synthesized using the Chemical Bath Deposition (CBD) and Chemical Vapor Deposition (CVD) methods, respectively, which in nanoscale, exhibit 1-dimensional structure and quantum confinement effects that lead to better properties. Prior to the synthesis process, the novel seed layer, which is the Mg0.3Zn0.7O thin film, is introduced.